Thea Stilton and the ice treasure - Battan, Alessandro, 1974-; Clement, Emily (Translator). (New York : Scholastic, 2011)
"In this fabumouse adventure, the Thea Sisters head to Alaska, where they're attending a conference held by an important ecological association. Their host and his family are native Alaskans, who show the mouselings their favorite games and activities. But soon there's trouble - the Thea Sisters discover that someone is upsetting the ecosystem by blowing up the ice with explosives! Can the Thea Sisters figure out what's going on and save the day?"--Publisher.
"Original title: Il tesoro di ghiaccio"--T.p. verso.
RL3.
007-010.
Keywords: Mice -- Juvenile fiction; Journalists -- Juvenile fiction; Mice -- Fiction; Ecology -- Fiction; Mice -- Fiction; Ecology -- Fiction; Alaska -- Juvenile fiction; Alaska -- Fiction; Alaska -- Fiction